2022
DOI: 10.32734/lingpoet.v3i1.6500
|View full text |Cite
|
Sign up to set email alerts
|

Translation Quality Assessment on Medan City Tourism Official Web Pages

Abstract: This research was conducted to analyze the quality of the translation on the Medan City Tourism web pages. In this research, the researcher used the translation quality assessment model proposed by Nababan et al. The TQA model by Nababan et al. focuses on three aspects, namely accuracy, acceptability, and readability. The final result of measuring these three aspects is the total value for the quality of the translation on a scale of 1-3. This research has the objectives to: 1) analyze the accuracy of the Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the same year, Pratama et al (2021) also used Nababan et al 's (2012) model as a foundation and discovered that translating tourism promotional texts' cultural references was challenging. Similarly, Putri et al (2022) investigated the translation of the Medan City Tourism website pages under the TAQ Nababan et al (2012) developed. Overall, the examined earlier research demonstrated the impact of semantic meanings on the quality of translation.…”
Section: Studies Trends On Cultural Referencesmentioning
confidence: 99%
“…In the same year, Pratama et al (2021) also used Nababan et al 's (2012) model as a foundation and discovered that translating tourism promotional texts' cultural references was challenging. Similarly, Putri et al (2022) investigated the translation of the Medan City Tourism website pages under the TAQ Nababan et al (2012) developed. Overall, the examined earlier research demonstrated the impact of semantic meanings on the quality of translation.…”
Section: Studies Trends On Cultural Referencesmentioning
confidence: 99%
“…That model has been widely used in several studies in assessing translation products. Some of the latest studies are conducted by Sofie & Ayuningtias (2023) on website articles of the Indonesia Embassy in Beijing, Fatariska (2023) on an article about Batik, Putri et al (2022) on city tourism official web page articles, and Naratama (2017) on journalistic text. Specifically for literary texts such as novels, the model was also used in studies conducted by H. Nugraha (2019), Ningsih et al (2020), and (Syah et al, 2023).…”
Section: Introductionmentioning
confidence: 99%